An unusual new species of Aulacus Jurine (Hymenoptera: Evanioidea: Aulacidae) from Southern Western Ghats, India - Kumar, P. Girish; Smith, David R.; Binoy, C. (Zootaxa, 2019)
Aulacus sahyadriensis Girish Kumar, Smith & Binoy sp. nov. is described from Kerala part of Southern Western Ghats, India. The species is illustrated and separated from other species of Aulacus known from the Oriental Region. It is the second species of Aulacus recorded from India. A key to species of Oriental Aulacus is provided.